Kajian Mutu dan Palatibilitas Silase dan Hay Ransum Komplit Berbasis Sampah Organik Primer pada Kambing Peranakan Etawah - Yusmadi Yusmadi; Nahrowi Nahrowi; Muhammad Ridla (Jurnal Agripet, 2008)
The quality and palatibility of silage and hay complete ration based on organic primer garbage in peranakan etawah (PE) poadABSTRACT. This research was conducted to study the quality and palatability of silage and hay complete ration based on organic primer garbage in nine heads of Peranakan Etawah (PE) Goat. The quality of silage and hay was evaluated By measuring pH, total number of lactic acid Bacteria (LAB), palatability, dry matter (DM) and organic matter (OM) aroma and color of silage. Nine heads of peranakan etawah were grouped based on their lactation periode and randomly assigned to one of tree dietary treatments. The treatments were (1) Control rations; (2) silage complete ration (SRK); and (3) Hay complete ration (HRK). The results indicated that the silage had PH 4.15 and total number of LAB was 2.4 x 10 cfu/g of silage. Dry matter and organic matter digestibility of SRK were better than those of HRK. The palatability of SRK was higher than HRK but less than control. Storage of SRK for did not change dry matter and organic matter content. Organoleptic analysis indicated that texture and color of HRK were changed at after storage, while SRK was still constant. It is concluded that silage composed of organic primer garbage has high quality in terms of physical, chemical and microbial characteristics, prolong storage.